Fructosylation generates neo‐epitopes on human serum albumin. Issue 5 (24th April 2015) - Allarakha, Shaziya; Ahmad, Parvez; Ishtikhar, Mohd; Zaheer, Mohammad Shoaib; Siddiqi, Sheelu Shafiq; Moinuddin; Ali, Asif
Abstract Hyperglycemia is the defining feature of diabetes mellitus. The persistently high levels of reducing sugars like glucose and fructose cause glycation of various macromolecules in the body. Human serum albumin (HSA), the most abundant serum protein with a myriad of functions, is prone to glycation and consequent alteration in its structural and biological properties. This study aimed to assess the role of fructose‐modified human serum albumin as a marker of diabetic pathophysiology. We carried out modification of HSA with fructose and the changes induced were studied by various physicochemical studies. Fructose modified‐HSA showed hyperchromicity in UV spectrum and increased AGE‐specific fluorescence as well as quenching of tryptophan fluorescence. In SDS‐PAGE protein aggregation was seen. Amadori products were detected by NBT. The fructose modified HSA had higher content of carbonyls along with perturbations in secondary structure as revealed by CD and FT‐IR. A greater hydrodynamic radius of fructose‐modified HSA was evident by DLS measurement. The fructose‐modified HSA induced high titre antibodies in experimental animals exhibiting high specificity towards the immunogen. © 2015 IUBMB Life, 2015 67(5):338–347, 2015